2022
DOI: 10.1097/mpg.0000000000003549
|View full text |Cite
|
Sign up to set email alerts
|

Education and Psychosocial Factors Predict Odds of Death After Transfer to Adult health Care in Pediatric Liver Transplant Patients

Abstract: Objectives:To analyze demographic, psychosocial, and clinical factors in pediatric liver transplant recipients for their association with death or loss to follow up in adulthood. We aimed to better understand known health disparities in transplant outcomes and identify potentially modifiable risk factors prior to transfer. Methods: A retrospective cohort study of children who underwent liver transplantation at a large tertiary transplant center and were transferred to adult care between 2000 and 2015.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Findings demonstrated higher rates of death in Black patients after transfer compared to other races (44% vs. 16%) and experienced about 50% mortality at 20 years post-LT (double that observed in White patients) [26]. They followed this with a retrospective single-center study identifying demographic, psychosocial, education, and clinical factors in pediatric LT patients that may be predictive of future death or loss to follow-up in adulthood [27]. Findings demonstrated that adult death was persistently associated with Black race (odds ratio, OR 6.59), substance use (2.81), and failure to graduate high school (OR 9.59) [27].…”
Section: Inequities Particular To the Pediatric Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings demonstrated higher rates of death in Black patients after transfer compared to other races (44% vs. 16%) and experienced about 50% mortality at 20 years post-LT (double that observed in White patients) [26]. They followed this with a retrospective single-center study identifying demographic, psychosocial, education, and clinical factors in pediatric LT patients that may be predictive of future death or loss to follow-up in adulthood [27]. Findings demonstrated that adult death was persistently associated with Black race (odds ratio, OR 6.59), substance use (2.81), and failure to graduate high school (OR 9.59) [27].…”
Section: Inequities Particular To the Pediatric Populationmentioning
confidence: 99%
“…They followed this with a retrospective single-center study identifying demographic, psychosocial, education, and clinical factors in pediatric LT patients that may be predictive of future death or loss to follow-up in adulthood [27]. Findings demonstrated that adult death was persistently associated with Black race (odds ratio, OR 6.59), substance use (2.81), and failure to graduate high school (OR 9.59) [27].…”
Section: Inequities Particular To the Pediatric Populationmentioning
confidence: 99%
“…Multiple demographic, clinical, and psychosocial factors from childhood are independently associated with adult death after pediatric LT. In a retrospective cohort study of 101 children who underwent LT and were transferred to adult care between 2000 and 2015, 93 followed with an adult provider, while 8 were lost to follow up (13). In total 23 of 93 patients died after transfer (24.7%).…”
Section: Educationmentioning
confidence: 99%
“…The paper appearing in this issue of JPGN by Stevens et al (5) which investigated the role played by numerous demographic, clinical, and psychosocial characteristics in the long-term outcome of pediatric liver transplant recipients transitioning to adult providers' care is therefore particularly welcome. In fact, the authors with a quite well-designed study add a new tile to this complex mosaic, which helps (a) to shed more light on the causes behind death and loss to FU after transition, (b) to risk-stratify adolescents and formulate as much as possible individualized future approaches to their transition of care.…”
Section: Insights On Transition Of Care-related Deaths Of Young Adult...mentioning
confidence: 99%
“…In summary and overall, it is evident that in this special population (1) long‐term issues, psychosocial aspects, quality of life and nonadherence are important issues with some still unmet goals, (2) no existing pediatric‐to‐adult care transition program after liver transplantation is perfect or adequately fulfilling all the planned requirements. Future formal transition programs could benefit from the results of the study of Stevens et al (5) in the early identification of high‐risk pediatric liver transplant recipients during the transfer to adult facilities, and in focusing on modifiable factors such as academic outcomes and substance abuse careful prevention. The same conclusions would probably be applicable to any adolescent with a chronic liver condition who will transition to an adult provider.…”
mentioning
confidence: 99%